Reactive media constructed wetland for phosphorus removal: assessing the opportunity and challenges - Murujew, Olga; Le Corre Pidou, Kristell; Wilson, Andrea; Bajón Fernández, Yadira; Vale, Peter C. J.; Jefferson, Bruce; Pidou, Marc (IWA Publishing, 2024)
Reactive media present an alternative to gravel in constructed wetlands and have the potential to sustainably and efficiently remove phosphorus from wastewater. In this study, a full-scale steel slag wetland has been operated for its whole lifecycle at which 1.39 mg P/g media were retained. During its lifecycle, this wetland met strict consents below 0.5 mg P/L for the first 6 months and was operated for 266 and 353 days before the effluent phosphorus concentration rose above the typical consents of 1 and 2 mg P/L, respectively. A detailed analysis of the system demonstrated that the performance was directly associated with the release of materials from the media into the water which in turn affected other critical parameters such as pH. Further analysis of the media suggested that greater understanding was needed concerning the role of carbonates and in particular calcite if steel slag is to be effectively managed for use on constructed wetlands. Importantly, controlled release of calcium oxide from the media surface is required by managing the concerns of pH and vanadium release.
Keywords: constructed wetland; reactive media; P removal; steel slag